Health behavior : (Jossey-Bass, 2015)
Health Behavior: Theory, Research, and Practice, Fifth Edition, is a thorough introduction to the practice of health education and health promotion, covering the theories, applications, and research of most use to public health students and practitioners. Through four editions, with more than 100,000 copies sold, this book has become the gold-standard textbook for health behavior courses. This essential resource includes the most current information on theory, research, and practice at individual, interpersonal, and community and group levels, with substantial new content on current and emerging theories of health communication, social marketing and e-health, culturally diverse communities, health promotion, the impact of stress, the importance of networks and community, social marketing, and evaluation. New contents include an update to the selection of theories, both established and emerging; e-health and social media as integrated into health communication; global health as an application of health behavior theory; culture and health disparities; more guidance on how to select suitable theories for specific problems/​issues. In addition to a selection of basic ancillary materials, the editors offer a dedicated website with student-written "theory in action" examples; expanded bibliographies; exemplar measures of theoretical constructs; and relevant links